Physicochemical Evaluation of Tempeh-Fish Sausage - T J Moedjiharto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Evaluation on the physicochemical property of “tempe-dumbo” sausage made from meat of Clarias gariepinus and tempeh flour has been carried out. Randomized design with tree replications were used. Sausages were prepared from tempeh flour and fish meat in the proportion of: 1:0; 1:0,2; 1:0,3; 1:10,4 and 1:0,5 (w /w). Hardness, total volatile bases (TVB), and taste were evaluated. The results showed that the proportion of flour tempeh influenced the content the quality of “tempe-dumbo” sausage in term of protein quality, TVB.and taste. The addition of tempeh flour had significant effect the decrease essential amino acids, of total amino acids content, and organoleptic ascore (taste and flavor). . “Tempeh-dumbo” sausage contained essential amino acid of 27,354 mg/ g, protein which was consisted of 7 essential amino acid. Key words : Sausage, tempeh, clarias gariepinus, protein quality.